2017
DOI: 10.18203/2320-6012.ijrms20174946
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intraperitoneal instillation of ropivacaine with normal saline in laparoscopic cholecystectomy

Abstract: Background: Local anesthetics are now widely used, as they have a good safety profile and are available in long acting preparation. They provide the benefit of analgesia without systemic side effects that may result from use of enterally and parenterally administered drugs.Methods: This prospective randomized double-blind study was conducted on 100 patients with symptomatic gall stones disease undergoing laparoscopic cholecystectomy. Patients were randomized to receive either 0.5% of 3mg/kg of Ropivacaine dilu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…A study by Bindra et al . [ 15 ] found that total analgesic requirement was significantly less in patients who received intraperitoneal instillation of drug before creation of pneumoperitoneum (1.34 ± 0.52 g paracetamol) than patients who received normal saline (4.7 ± 0.97 g paracetamol). Cu et al .…”
Section: Discussionmentioning
confidence: 99%
“…A study by Bindra et al . [ 15 ] found that total analgesic requirement was significantly less in patients who received intraperitoneal instillation of drug before creation of pneumoperitoneum (1.34 ± 0.52 g paracetamol) than patients who received normal saline (4.7 ± 0.97 g paracetamol). Cu et al .…”
Section: Discussionmentioning
confidence: 99%